2018
DOI: 10.3390/app8081336
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Microbial Remediation of Heavy Metals in Soil: A Critical Review

Abstract: The use of microbes to change the concentration of heavy metals in soil and improve the ability of plants to deal with elevated metals concentrations has significant economic and ecological benefits. This paper reviews the origins and toxic effects of heavy metal pollution in soil, and describes the heavy metal accumulation mechanisms of microbes, and compares their different bioconcentration abilities. Biosorption, which depends on the special structure of the cell wall, is found to be the primary mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(75 citation statements)
references
References 69 publications
0
64
0
1
Order By: Relevance
“…Microbial remediation refers to decreasing the availability of Pb in the environment using indigenous/exotic microbes. Bacterial species such as Alcaligenes sp., Bacillus firmus, Bacillus licheniformis, Enterobacter cloacae, Escherichia coli, Micrococcus luteus, Pseudomonas fluorescens, and Salmonella typhi show adsorption potential of Pb from the contaminated resources [219][220][221][222][223]. Wang et al [224] concluded that bacterial strain B38 (mutant of Bacillus subtilis) has immense potential to remediate heavy metals including Pb in China.…”
Section: Microbial Remediationmentioning
confidence: 99%
“…Microbial remediation refers to decreasing the availability of Pb in the environment using indigenous/exotic microbes. Bacterial species such as Alcaligenes sp., Bacillus firmus, Bacillus licheniformis, Enterobacter cloacae, Escherichia coli, Micrococcus luteus, Pseudomonas fluorescens, and Salmonella typhi show adsorption potential of Pb from the contaminated resources [219][220][221][222][223]. Wang et al [224] concluded that bacterial strain B38 (mutant of Bacillus subtilis) has immense potential to remediate heavy metals including Pb in China.…”
Section: Microbial Remediationmentioning
confidence: 99%
“…Microorganisms, which are mostly prokaryotic, participate in redox reactions and change the valance of heavy metals, and thereby, change their activity, which can affect their mobility or toxicity (37). For example, microorganisms such as Rhizopus can absorb heavy metal ions in the soil and Thiobacillus can absorb heavy metal ions as well as inorganic ions, such as S, which combine with the metal ions to form a precipitate that can be separated from the soil (44).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble cadmium can be reduced by chemically aided microbes or fixed by microbial absorption thus affecting plant absorption of cadmium (Meng et al., ). The metabolism of microbes produces secretions, such as organic acids, that can dissolve cadmium and other heavy metals in soil; therefore, adding microbial species to the soil, such as bacteria and fungi, can aid in the reduction of soil cadmium (Jin, Luan, Ning, & Wang, ). Cadmium also binds strongly to soils with higher organic matter (higher cation exchange capacity) making cadmium less available to plant life (ATSDR, ; Roberts, ).…”
Section: Cadmium In Plantsmentioning
confidence: 99%